Anggaran Penjualan Dan Pengendalian Tingkat Produksi: Simulasi Teoritik - NFN Husnayetti (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2013)
Budget is one of the tools for management in carrying out its functions, especially in the planning and controlling. With the formulation of the budget of a company, it can be used as a basis for assessing the performance of the company by the budgets prepared by the realization.